Science formative assessment : 75 practical strategies for linking assessment, instruction, and learning (Vol. 1) - Keeley, Page. (Thousand Oaks, California : Corwin, 2016)
In this essential resource, science educator Page Keeley provides teachers with guidance, suggestions and techniques for using formative assessment to improve teaching and learning in the science classroom.
Vol. 1.
Includes bibliographical references and index.
Keywords: Science -- Study and teaching -- Evaluation; Interaction analysis in education; Creative ability in science; Curriculum planning; Effective teaching